2023
DOI: 10.3390/su15032500
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Circular Economy Design Guidelines for the Australian Built Environment Sector

Abstract: The construction and demolition (C&D) waste stream is the main source of solid waste in Australia. While there is a strong circularity drive in Australia’s and state/territory governments’ waste regulatory framework, clear guidelines for C&D waste management are yet to be developed for the built environment sector in Australia. This study proposes a suite of construction industry-specific guidelines for achieving circular economy (CE) goals by reviewing issues related to “Design for Zero Waste” (DfZW) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…In particular, China has currently dominated this research area, possibly because it is one of the early adopters of the CE as a national development strategy to tackle environmental problems(Sauvé et al, 2016). Australia ranks the second in terms of research output showing their active response to the fact that the construction & demolition waste in Australia is higher than the global average(Zaman et al, 2023). This world mapping also conforms with andMunaro et al (2020) who revealed the leading role of the UK in Europe.…”
supporting
confidence: 68%
“…In particular, China has currently dominated this research area, possibly because it is one of the early adopters of the CE as a national development strategy to tackle environmental problems(Sauvé et al, 2016). Australia ranks the second in terms of research output showing their active response to the fact that the construction & demolition waste in Australia is higher than the global average(Zaman et al, 2023). This world mapping also conforms with andMunaro et al (2020) who revealed the leading role of the UK in Europe.…”
supporting
confidence: 68%
“…This result is well-aligned with the study carried out by [35] in which design for disassembly and design for adaptability and flexibility are identified as strategies cited by every author. The main aim of design for disassembly is to provide the ability to carefully disassemble building components to maximise the potential reuse and recovery of building components and materials [51]. Design with high-quality, longperforming components is essential in order to increase the durability of the design and it directly impacts on the next-service life of the particular product or component [23].…”
Section: Surveys + Expert Forumsmentioning
confidence: 99%
“…Waste management is another aspect that needs to be considered during construction and many studies have identified that proactive waste management is better than reactive waste management. It has been identified that innovative processes and concepts have taken the lead in reducing waste generated at construction sites [51]. However, the authors opined that these in-site waste management options may incur additional costs; thus, a better analysis of positive and negative impacts should be considered before implementing the same.…”
Section: Surveys + Expert Forumsmentioning
confidence: 99%
“…Generative aids support the integration of circular strategies or options during the design process [19]. Several authors have contributed to the development of design guidelines for a circular built environment, with an emphasis on achieving optimal environmental performance [19][20][21][22][23]. A similar focus on environmental performance is found in the study by Kręt-Grześkowiak et al [24], who reviewed 70 articles that offer guidelines for design for disassembly and design for adaptability and proposed a design process framework.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these articles did not study circular building components. Van Stijn et al [19,20], Eberhardt et al [22], and Zaman et al [23] did develop aids specifically for circular building components, and van Stijn and Gruis [12] reviewed 36 existing generative design aids and developed the "Circular Building Components Generator" (CBC generator), a generative tool for circular building components.…”
Section: Introductionmentioning
confidence: 99%